Mengoptimalkan Motivasi Belajar Bernyanyi Anak (Mengatasi Kecemasan Dengan Gerakan Tematis) - Dukha Yunitasari; Hary Murcahyanto (Journal of Elementary School (JOES), 2023)
This study aims to describe the relationship between anxiety levels and motivation to learn singing with thematic movements in early childhood. This type of research is ex post facto type causal research or correlation research with a quantitative approach. The population in this study were children aged 5-6 years as many as 30 children. The sampling technique used in this study was Simple Random Sampling with group A at NW Pancor Kindergarten as a research sample of 15 children. The data collection technique used a questionnaire. Data were analyzed using Pearson product-moment correlation. The results showed that there was a negative correlation between the level of anxiety and motivation to learn singing with thematic movements of students because r-count> r-table which is 0.85> 0.482, which means Ho is rejected. The conclusion of this study is that there is a significant relationship between anxiety levels and motivation to learn singing with thematic movements in early childhood at NW Pancor Kindergarten, which indicates that the learning approach is effective in increasing learning motivation and reducing children's anxiety levels. Keywords: Early childhood, Singing, Anxiety, Motivation